Development and Implementation of a New Telerehabilitation System for Audiovisual Stimulation Training in Hemianopia - Tinelli, Francesca; Cioni, Giovanni; Purpura, Giulia (Frontiers in Neurology, 2017)
Telerehabilitation, defined as the method by which communication technologies are used to provide remote rehabilitation, although still underused, could be as efficient and effective as the conventional clinical rehabilitation practices. In the literature, there are descriptions of the use of telerehabilitation in adult patients with various diseases, whereas it is seldom used in clinical practice with child and adolescent patients. We have developed a new audiovisual telerehabilitation (AVT) system, based on the multisensory capabilities of the human brain, to provide a new tool for adults and children with visual field defects in order to improve ocular movements toward the blind hemifield. The apparatus consists of a semicircular structure in which visual and acoustic stimuli are positioned. A camera is integrated into the mechanical structure in the center of the panel to control eye and head movements. Patients can use this training system with a customized software on a tablet. From hospital, the therapist has complete control over the training process, and the results of the training sessions are automatically available within a few minutes on the hospital website. In this paper, we report the AVT system protocol and the preliminary results on its use by three adult patients. All three showed improvements in visual detection abilities with long-term effects. In the future, we will test this apparatus with children and their families. Since interventions for impairments in the visual field have a substantial cost for individuals and for the welfare system, we expect that our research could have a profound socio-economic impact avoiding prolonged and intensive hospital stays.